2021
DOI: 10.3390/brainsci11070923
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic Traits in Childhood: Insights from Parental Warmth and Fearless Temperament via Conscience Development

Abstract: The role of psychopathic traits in predicting more serious and persistent patterns of child conduct problems has been well documented. The jointly presence of interpersonal (grandiose–deceitful), affective (e.g., callous–unemotional), and behavioral psychopathic traits (impulsive–need of stimulation) identifies a group of children at increased risk of psychosocial maladjustment. The present study aims to disentangle the underlying mechanisms by examining how early parenting (i.e., warmth) and child temperament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 74 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…Biological factors are innately determined and cannot be changed, while environmental factors are closely related to acquired interventions and educations. Studies [ 43 , 44 ] have shown that children’s temperament is genetically determined and influenced by environmental factors, it is difficult to distinguish between the 2. The nurses can communicate with the children’s family members and main caregivers to explain that the success of the operation is only the first step to the success of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Biological factors are innately determined and cannot be changed, while environmental factors are closely related to acquired interventions and educations. Studies [ 43 , 44 ] have shown that children’s temperament is genetically determined and influenced by environmental factors, it is difficult to distinguish between the 2. The nurses can communicate with the children’s family members and main caregivers to explain that the success of the operation is only the first step to the success of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…This lower arousal also includes a reduction in the perception and sensitivity to fear signals from others, which may cause difficulties in learning empathy and guilt that, in turn, may cause socialization problems [9][10][11][12]. Thus, prosocial learning difficulties and insensitivity to punishment might lead children with a fearless temperament to seek out stimulating new situations, such as dangerous or antisocial behaviors that may increase the risk of developing CP [13][14][15][16][17].…”
Section: Back To the Origin: The Role Of Fearlessnessmentioning
confidence: 99%
“…Previous evidence has shown how low parental warmth and fearlessness predict later psychopathic traits in children at increased risk of psychosocial maladjustment. The two-year follow-up study conducted by López-Romero and colleagues [ 4 ] on a very large cohort of preschoolers aged 3 to 6 years aimed to disentangle how these factors interact with each other to predict the later occurrence of psychopathic traits. Direct effects from fearlessness to interpersonal and behavioral psychopathic traits were identified, as well as a negative effect of parental warmth, fearless temperament, and their interaction on the development of individual conscience, which in turn mediated the indirect effect of these variables on psychopathic traits.…”
Section: Child Temperament Parenting Style and Family Functioningmentioning
confidence: 99%
“… Colombia, Spain Universidad de la Costa, Universidad Europea de Madrid Article [ 3 ] Catone G, Almerico L, Pezzella A, Riccio MP, Bravaccio C, Bernardo P, Muratori P, Pascotto A, Pisano S, Senese VP. Italy Suor Orsola Benincasa University, University of Campania “Luigi Vanvitelli”, Federico II University, Santobono-Pausilipon Children Hospital, IRCCS Stella Maris Foundation Article [ 4 ] López-Romero L, Cutrín O, Maneiro L, Domínguez-Álvarez B, Romero E. Spain, Netherlands Universidade de Santiago de Compostela, Leiden University Article [ 5 ] Smorti M, Inguaggiato E, Vezzosi L, Milone A. Italy University of Pisa, IRCCS Stella Maris Foundation Article [ 6 ] Marzilli E, Cerniglia L, Cimino S. Italy University of Rome “La Sapienza”, International Telematic University Uninettuno Article [ 7 ] Fantozzi P, Sesso G, Muratori P, Milone A, Masi G. Italy IRCCS Stella Maris Foundation, University of Pisa Systematic Review [ 8 ] Balia C, Carucci S, Milone A, Romaniello R, Valente E, Donno F, Montesanto A, Brovedani P, Masi G, Glennon JC, Coghill D, Zuddas A, The Matrics Consortium.…”
Section: Table A1mentioning
confidence: 99%